Improved detection methods significantly increase the detection window for EPO microdoses. Issue 1 (9th August 2020) - Martin, Laurent; Martin, Jean‐Antoine; Collot, David; Hoang, Olivier; Audran, Michel; Ericsson, Magnus; Marchand, Alexandre
Abstract: To reproduce a potential doping scenario, a 2 week administration of recombinant erythropoietin (rEPO) microdoses alone or in combination with growth hormone (GH) microdoses (three times a week) was performed on healthy and athletic male subjects. The aim of this study was to evaluate the identification capability of rEPO in samples obtained during and post treatment. Detection was tested in urine and blood using the antidoping techniques for rEPO detection (iso‐electric focusing (IEF)‐, sodium‐dodecyl‐sulfate (SDS)‐polyacrylamide gel electrophoresis (PAGE) and for some urine samples the sarcosyl (SAR)‐PAGE method) with some improvements: for blood samples, instead of a simple concentration step, immuno‐extraction of EPO was performed for all urines to limit protein contamination that can affect migration. In addition, elution buffer modifications also improved the quality of migration. The use of a recently validated biotinylated anti‐EPO antibody simplified the protocols, allowing a single transfer step instead of a double‐blot even by IEF with a lowered background. The criteria for suspicious blood and urine samples by IEF were also re‐evaluated. While endogenous EPO was not decreased over the course of the study, EPO microdoses were detectable in blood and urine between 24 h and 72 h after an administration. Detection in urine in combination with SDS‐PAGE was the most sensitive combination for prolonged detection (100% identification after 48 h, 91% after 72 h), slightly better than IEF. Urine samples also tested by SAR‐PAGE indicated a similar sensitivity of detection to SDS‐PAGE. GH co‐administration had no impact on rEPO elimination/detection. Abstract : Repeated administration of EPO microdoses did not decrease the level of endogenous EPO. However, EPO microdoses were detectable in blood (serum) and urine between 24 h and 72 h after an administration. Detection in urine in combination with SDS‐PAGE was the most efficient for prolonged identification (up to 72 h for 91% of the samples).